"Enzyme‐Like" Spatially Fixed Polyhydroxyl Microenvironment‐Activated Hydrochromic Molecular Switching for Naked Eye Detection of ppm Level Humidity. Issue 1 (23rd November 2022) - Wei, Xiaoyan; Zhang, Sean Xiao‐An; Sheng, Lan
Abstract: The detection and monitoring of ultralow humidity (<100 ppm) are critical in many important industries, such as high‐tech manufacturing, scientific research, and aerospace. However, the development of ppm level humidity sensors with portability, low cost, and ease of regeneration remains a significant challenge. Herein, an innovative "enzyme‐like" construction strategy is proposed to address this problem by employing suitable molecular‐level humidity‐sensitive units and chemically constructing a multilevel spatial synergistic sensitization microenvironment around it. The as‐prepared ultralow humidity‐sensitive paper (UHSP) achieved a naked eye recognition humidity of 0.01–100 ppm. UHSP not only is simple to prepare, handy and low‐cost, but can also be simply and efficiently regenerated as well as recycled many times by skillfully utilizing the "unconventional sublimation" and "lime slaked" of calcium oxide. The molecular reaction mechanisms involved in the humidity response and regeneration of UHSP have been demonstrated in detail. UHSP can provide a promising new method for ultralow humidity detection in the form of portable kits or sirens. The demonstrated "enzyme‐like" construction strategy can bring unlimited ideas and implications to the design and development of sensors with tunable response thresholds, particularly high sensitivity. Abstract : An "enzyme‐like" construction strategy for ultralow humidity‐sensitive paper (UHSP) is proposed, which activates hydrochromic molecular switching by constructing a spatially‐fixed polyhydroxyl microenvironment. As a result, recyclable naked eye recognition of 0.01–100 ppm humidity is achieved first. This UHSP provides a more economical, environmental friendly and convenient choice for ultralow humidity monitoring required by high‐tech manufacturing such as chips, solar cells, etc.